Respostas
respondido por:
1
Vou usar ^ como elevado a
a=10^-4
b= 10^-4
c=10^3
a)a.b.c
10^-4x10^-4x10^3=
10^(-4-4+3)=
10^-5
b)a.b^2
10^-4x(10^-4)^2=
10^-4x10^-8=
10^(-4-8)=
10^-12
c)a^2.b^2/c^3
(10^-4)^2x(10^-4)^2/(10^3)^3=
10^-8x10^-8/10^9=
10^(-8-8-9)=
10^-25
a=10^-4
b= 10^-4
c=10^3
a)a.b.c
10^-4x10^-4x10^3=
10^(-4-4+3)=
10^-5
b)a.b^2
10^-4x(10^-4)^2=
10^-4x10^-8=
10^(-4-8)=
10^-12
c)a^2.b^2/c^3
(10^-4)^2x(10^-4)^2/(10^3)^3=
10^-8x10^-8/10^9=
10^(-8-8-9)=
10^-25
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás